Penerapan Pijat Bayi Terhadap Kualitas Tidur pada Bayi Usia 0-6 Bulan di Wilayah Kerja Puskesmas Pucangsawit Kota Surakarta - Sevi Lestiya Rini Handayani; Maryatun Maryatun (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Background: The prevalence of sleep problems in infants in Indonesia reaches 44.2%, often waking up at night. In Central Java in 2018, 44% of infants experienced similar sleep disorders. Fulfilling sleep needs is important for their development. Infant massage is an effective non-pharmacological therapy to improve sleep quality. Objective: Knowing the changes in sleep quality in two respondents before and after the application of baby massage. Objective: Knowing the changes in sleep quality in two respondents before and after the application of baby massage. Methods: This research used descriptive method with case study approach. Measurements were made on 2 respondents to determine the quality of sleep using BISQ and the application was carried out with baby massage 3 times a week for 2 weeks. Results: There was an improvement in sleep quality in By. S from BISQ score 7 to score 15 and By. A also experienced an increase in sleep quality from BISQ score 6 to 14. Conclusion: Infant massage can be applied to improve the sleep quality of infants aged 0-6 months.